Assessment of subclinical magnesium deficiency in pregnant women - S. V. Orlova; E. A. Nikitina; N. V. Balashova; A. N. Isaev; A. V. Ershov; O. E. Pronina; A. N. Vodolazkaya; E. V. Prokopenko (Медицинский совет, 2022)
Introduction. The question of the ratio of calcium and magnesium in the body in the scientific community is not discussed as often as the role of each of these elements. Experts pay even less attention to the ratio of minerals in the body of pregnant women.Aim. To analyze the content of magnesium and calcium in the blood of pregnant women at different gestation periods and evaluate the ratio of magnesium / calcium in order to establish the calculated coefficient.Materials and methods. 272 pregnant women (age 31.85 ± 5.0 years) at different gestation periods were included in the study. The subjects did not complain, typical for the clinic of magnesium and calcium deficiency. All surveyed gave written consent to the study. A biochemical blood test (determination of the concentration of total calcium, magnesium) was carried out in the laboratory of LLC DNKOM in Moscow. Blood sampling from the cubital vein was carried out according to the standard method in the morning on an empty stomach after 10–12 hours of fasting.Results and discussion. Concentration of  total calcium in  the serum was (M  ±  SD) 2.28  ±  0.11  mmol/l, total magnesium  – 0.78 ± 0.07 mmol/l, magnesium/calcium ratio – 0.34 ± 0.03. Mean concentrations of calcium and magnesium were significantly lower in women in the II and III trimesters compared with the I trimester (p < 0.001). A decrease in magnesium concentration below the optimal for pregnant women of 0.8 mmol / l was observed in 37.5% of women in the first trimester, in 77.3% and 84.1% in the II and III trimesters, respectively. Serum magnesium concentration less than 0.7 mmol / l, reflecting a profound magnesium deficiency, was detected in the first trimester in 3.6% of women, in the second trimester – in 11.3% of women, in the third trimester – in 15.9% of pregnancies. Hypocalcemia (total calcium concentration less than 2.15 mmol/l) was recorded in 0.9%, 11.3% and 22.3% of pregnant women in the I, II and III trimesters. When calculating the magnesium/calcium ratio, subclinical magnesium deficiency was detected in 96.7% of pregnant women throughout pregnancy. Conclusion. The data obtained indicate the need for pregravid examination and early correction of metabolic disorders.>< 0.001). A decrease in magnesium concentration below the optimal for pregnant women of 0.8 mmol / l was observed in 37.5% of women in the first trimester, in 77.3% and 84.1% in the II and III trimesters, respectively. Serum magnesium concentration less than 0.7 mmol / l, reflecting a profound magnesium deficiency, was detected in the first trimester in 3.6% of women, in the second trimester – in 11.3% of women, in the third trimester – in 15.9% of pregnancies. Hypocalcemia (total calcium concentration less than 2.15 mmol/l) was recorded in 0.9%, 11.3% and 22.3% of pregnant women in the I, II and III trimesters. When calculating the magnesium/calcium ratio, subclinical magnesium deficiency was detected in 96.7% of pregnant women throughout pregnancy.Conclusion. The data obtained indicate the need for pregravid examination and early correction of metabolic disorders